O-017 Preliminary Experience with a New Barrel Shaped Bifurcation Aneurysm Bridging Device. (14th July 2013) - Tateshima, S; Niemann, D; Moskowitz, S; Baxter, B; Frei, D
Abstract : Purpose: To test the feasibility of a novel fully retrievable barrel-shaped vascular reconstruction device for stent assisted endovascular treatment of wide-necked bifurcation aneurysms. Methods: 16 Canine were utilised to assess the acute technical feasibility and the chronic in vivo performance of the Barrel™ Bifurcation Vascular Reconstruction Device (Reverse Medical Corporation, Irvine, CA). The degree of angiographic aneurysm occlusion and the ability of the barrel device to support an embolic coil mass in both surgically created wide-necked (> 4 mm/dome to neck ratio < 2) bifurcation (n =16) and lateral wall (n =16) aneurysms were evaluated. Diagnostic angiography was performed during the procedure, immediately post procedure, and at 1, 2, 3, and 6 months post implantation. Histological analyses to evaluate vessel wall injury, inflammation, and neointimal response, were performed after 3 months on a subset of canines. Results: 32 surgically created wide necked (5.20 ± 0.61 mm/dome to neck ratio 1.47 ± 0.18) bifurcation and lateral wall aneurysms were successfully embolised with Barrel Vascular Reconstruction devices and embolic coils. All embolisations were deemed clinically acceptable with angiographic fills of 92% ± 10.2% and Coil packing densities of 49 ± 9%. Coil Protrusion was noted in 2/32 (6%) with small neck remnants seen in 13/32 (41%). Acute results demonstrated the device to be easily delivered through a microcatheter with excellent fluoroscopic visualisation of the device including the barrel segment. In all cases the device was easy to position with good coil mass support and device stability. As the device is resheathable, it could be placed into either the contralateral or ipso-lateral vessel of the bifurcation aneurysm, depending on which vessel position offered the best neck coverage. Additionally the device could be manipulated in situ to further gain optimal neck coverage. The 1, 2, 3 and 6-month angiographic follow-ups confirmed that the device continued to provide both coil mass stability and neck coverage. 3-month histology was conducted and demonstrated that the device had zero or minimal vessel wall damage, with mature, stable and endothelialised neointima at aneurysmal necks. Additionally device struts were associated with zero or minimal inflammatory reaction. Conclusions: The acute technical feasibility and chronic durability of the novel the Barrel™ Bifurcation Vascular Reconstruction Device has been demonstrated and may offer a new tool for the endovascular treatment of wide-necked bifurcation and branching type aneurysms. Disclosures: S. Tateshima: 2; C; Reverse Medical. 4; C; Reverse Medical. D. Niemann: 2; C; Reverse Medical. S. Moskowitz: 2; C; Reverse Medical. B. Baxter: 2; C; Reverse Medical. D. Frei: 2; C; Reverse Medical.